Safety and Efficacy of Tafenoquine for Plasmodium vivax Malaria Prophylaxis and Radical Cure: Overview and Perspectives - Markus MB (Dove Medical Press, 2021)
Miles B Markus1,2 1School of Animal, Plant and Environmental Sciences, Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa; 2Wits Research Institute for Malaria, School of Pathology, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South AfricaCorrespondence: Miles B MarkusWits Research Institute for Malaria, School of Pathology, Faculty of Health Sciences, University of the Witwatersrand, 7 York Road, Parktown, Johannesburg, 2193, South AfricaTel +27 794580773Fax +27 117892950Email medsynth@yahoo.co.ukAbstract: This article is inter alia a brief, first-stop guide to possible adverse events (AEs) associated with tafenoquine (TQ) intake. Safety and efficacy findings for TQ in Plasmodium vivax malaria prophylaxis and radical cure are summarized and some of the latest TQ-related studies (published in 2020 and 2021) are highlighted. In addition, little-known biological and other matters concerning malaria parasites and 8-aminoquinoline (8-AQ) drug action are discussed and some correct terminology pertinent to malaria is explained.Keywords: chloroquine, G6PD, hypnozoite, primaquine, relapse, WR238605